Extraction of compound nouns in Malay noun phrases using a noun phrase frame structure - Suhaimi Ab Rahman,; Nazlia Omar,; Mohd Juzaiddin Ab Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2014)
This paper addresses the process of extracting compound nouns in Malay noun phrases using a noun phrase frame structure. Studying in a compound noun area is very important to see the dependency of the word that can produce a correct meaning of the sentence. Each complete sentence in Malay must have their respective compound nouns. The compound nouns can be extracted from a subject and predicate of the sentences. The subject must consist of a noun phrase, while the predicate may have a verb phrase, an adjective phrase or a prepositional phrase. In a compound noun structure, we may know the head and modifier of the sentences. The compound noun has been discussed in detail by our native language experts. Many issues were highlighted to further strengthen the concept of compound nouns. Based on the issues discussed, we attempted to use a noun frame structure technique using a computer to extract compound nouns.